Implementation of a Mobile Application for GPS-Based Reporting of Water Pollution and Invasive Species - Muchammad Hasbi Ashshiddiqi; Muhammad Fahrie (bit-Tech, 2025)
Water pollution and the spread of invasive species threaten Indonesian river ecosystems, yet public participation in monitoring remains limited, often due to the lack of a centralized and accessible reporting tool. This study develops and validates a mobile platform to address this gap. Its primary contribution is a novel dual-reporting model, allowing the public to report both pollution incidents and invasive species findings using a single GPS-based application. This integrated approach provides a more holistic dataset than single-issue tools, critically enabling the future analysis of ecological links between pollution hotspots and invasive species outbreaks. The application was developed using Flutter for cross-platform accessibility and Supabase as a Backend as a Service to ensure scalability and rapid development. The main finding, confirmed through Black Box testing, is a functional prototype where all core user-side features, such as registration, login, and GPS report submission, performed successfully. This outcome validates the system's technical feasibility and the practical viability of using non-experts for data collection. While user-side functionality is proven, the report management functionality for administrators remains in the early stages. This research provides a viable tool for agencies to gather real-time field data. It also supports future development focused on a comprehensive admin dashboard, which is essential for report validation, data aggregation, and trend analysis, ultimately enhancing the system's effectiveness.